Single crystalline semi-nanotubes of indium germanate - Yan, Chaoyi (2012)
Single crystalline In2Ge2O7 nanotubes were synthesized by a thermal evaporation method. The growth mechanism of those novel seminanotubular structures was explained to be a vapor−liquid−solid (VLS) mechanism. Its morphology and structures were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy dispersive spectroscopy (EDS). The semi-nanotubes have widths of 80−500 nm and lengths of 5−20 μm. As-synthesized products were found to be single crystalline In2Ge2O7 with a monoclinic crystal structure. Indium particles serve as catalysts to direct nanotube growth. Germanium concentration nonuniformity is proposed to be the reason for a semi-nanotubular structure nucleation rather than nanotubes or nanowires.